Ambient fine particulate matter exposure and incident mild cognitive impairment and dementia. Issue 8 (26th April 2021) - Sullivan, Kevin J.; Ran, Xinhui; Wu, Fan; Chang, Chung‐Chou H.; Sharma, Ravi; Jacobsen, Erin; Berman, Sarah; Snitz, Beth E.; Sekikawa, Akira; Talbott, Evelyn O.; Ganguli, Mary
Abstract: Background/Objective: Poor air quality is implicated as a risk factor for cognitive impairment and dementia. Few studies have examined these associations longitudinally in well‐characterized population‐based cohorts with standardized annual assessment of both mild cognitive impairment (MCI) and dementia. We investigated the association between estimated ambient fine particulate matter (PM2.5 ) and risk of incident MCI and dementia in a post‐industrial region known for historically poor air quality. Setting/Participants: Adults aged 65+ years in a population‐based cohort ( n = 1572). Measurements: Census tract level PM2.5 from Environmental Protection Agency (EPA) air quality monitors; Clinical Dementia Rating (CDR)®. Design: We estimated ambient PM2.5 exposure (μg/m 3, single‐year and 5‐year averages) by geocoding participants' residential addresses to census tracts with daily EPA PM2.5 measurements from 2002 to 2014. Using Bayesian spatial regression modeling adjusted for age, sex, education, smoking history, and household income, we examined the association between estimated PM2.5 exposure and risk of incident MCI (CDR = 0.5) and incident dementia (CDR ≥ 1.0). Results: Modeling estimated single‐year exposure, each 1 μg/m 3 higher ambient PM2.5 was associated with 67% higher adjusted risk of incident dementia (hazard ratio [HR] = 1.669, 95% credible interval [CI]: 1.298, 2.136) and 75% higher adjusted risk of incident MCI (HR = 1.746, 95% CI: 1.518, 2.032). Estimates were higher when modeling 5‐year ambient PM2.5 exposure for incident dementia (HR = 2.082, 95% CI: 1.528, 3.015) and incident MCI (HR = 3.419, 95% CI: 2.806, 4.164). Conclusions: Higher estimated ambient PM2.5 was associated with higher risk of incident MCI and dementia, particularly when considering longer‐term exposure, and independent of demographic characteristics and smoking history. Targeting poor air quality may be a reasonable population‐wide intervention to reduce the risk of cognitive impairment in older adults, particularly in regions exceeding current recommendations for safe exposure to PM2.5 .